Propuesta de mejora en la producción de cerveza artesanal rubia a nivel semi-industrial a base de la unión de dos maltas para la empresa Milenaria (2019)
Milenaria, located in the Antonio Nariño locality in Bogotá Colombia, is a company dedicated to the manufacture and sale of craft beer, it has the need to increase and improve its production. Due to the high demand that it currently presents, in its manufacturing process it has had disadvantages due to the need to improve stages such as maceration, milling, boiling, filtration, fermentation, among others; If these stages are not improved, a decrease in production variables will be generated, such as time, quality and quantity of the final product and even losses of production batches. For the improvement of the process, a diagnosis will be made of each of the stages of the production of blond Ale beer in the Millennial plant and a bibliographic analysis will be carried out, selecting the most appropriate alternative and implementing it; an improvement in physical, chemical and organoleptic analysis will be evident. Finally, a cost analysis of the implemented alternative will be carried out, demonstrating a general improvement in the production process, that is, the stages implemented in beer production, the characteristics of the final product and the profitability of the process will be analyzed.